The Impact of Bank Image on Customer Loyalty: Bank Syariah Indonesia (BSI) - A. Iedar Zulfikar FQ; Imamul Hakim; Afifah Nur Millatinac (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The role of Islamic banks in the economic development of every country, including Indonesia, is so large that almost every sector related to financial activities requires various banking services. This study aims to determine the effect of service quality, bank image, and customer satisfaction on customer loyalty at Bank Syariah Indonesia Branch Office Dinoyo Malang. This research uses associative quantitative analysis. The population in this study is the customers of the BSI Dinoyo Malang Branch Office, which is approximately 17.000 customers. The sampling is as many as 100 customers. The data analysis technique used Structural Equation Modeling (SEM) analysis technique. Collecting data using a list of questionnaires. The results showed that service quality and customer satisfaction harmed customer loyalty, and bank image positively affected customer loyalty.